Sweet spot mapping and structural connectivity in subthalamic stimulation: predicting neuropsychiatric outcomes in Parkinson’s disease - Yan, Jiuqi; Sun, Jian; Wei, Xiang; Qiu, Chang; Zhao, Liang; Luo, Bei; Dong, Wenwen; Liu, Jingxuan; Lu, Guanghan; Zhang, Wenbin (Frontiers in Neuroscience, 2025)
ObjectiveSTN-DBS is an effective treatment for Parkinson’s disease (PD), improving motor symptoms, but its impact on non-motor symptoms, such as anxiety and depression, remain unclear. This study investigates the relationship between electrode contact locations, their corresponding volume of tissue activated (VTA), and postoperative changes in emotional symptoms. It aims to identify optimal group-level stimulation sites for improving anxiety and depression in PD patients and to develop a structural connectome to explore how cortical regions targeted by fiber projections correlate with mood outcomes.MethodsWe retrospectively studied 56 PD patients who underwent bilateral STN-DBS, assessed 6 months post-surgery. Standardized scales evaluated motor, affective, and cognitive symptoms before and after the procedure. Electrode positions were reconstructed using Lead-DBS, and VTAs were calculated. Voxel-wise sweet spot and structural connectivity analyses investigated how stimulation sites influenced clinical outcomes.ResultsCompared to preoperative assessments, postoperative evaluations revealed varying degrees of improvement in motor function, quality of life, and symptoms of anxiety and depression in PD patients (p < 0.05). The amelioration of anxiety and depression was associated with electrode contacts located in the ventral region of the STN. Specifically, improvements in anxiety were positively correlated with the VTA in the limbic region of the right STN. Sweet spot analysis revealed that stimulation of the ventrocentral region of the left STN was significantly associated with emotional improvement. Structural connectivity analysis revealed that fiber tracts to the prefrontal cortex (PFC) were positively associated with anxiety and depression improvement, while those to the sensorimotor cortex (SMC) showed a negative correlation.ConclusionSTN-DBS markedly improves motor symptoms and quality of life in PD patients while also positively impacting anxiety and depressive symptoms. The ventral STN is likely the optimal stimulation target for ameliorating anxiety and depressive symptoms. The therapeutic effects of STN-DBS electrodes may promote postoperative improvements in anxiety and depression by modulating fiber tracts connected to prefrontal regions. Future research should leverage connectome mapping and isolated fiber tracts to refine electrode placement, using directional leads to target specific STN subregions for improved symptom management.